Eye of the Beholder: Stage Entrance Behavior and Facial Expression Affect Continuous Quality Ratings in Music Performance - Waddell, George; Williamon, Aaron (Frontiers in Psychology, 2017)
Judgments of music performance quality are commonly employed in music practice, education, and research. However, previous studies have demonstrated the limited reliability of such judgments, and there is now evidence that extraneous visual, social, and other ‘non-musical’ features can unduly influence them. The present study employed continuous measurement techniques to examine how the process of forming a music quality judgment is affected by the manipulation of temporally specific visual cues. Video footage comprising an appropriate stage entrance and error-free performance served as the standard condition (Video 1). This footage was manipulated to provide four additional conditions, each identical save for a single variation: an inappropriate stage entrance (Video 2); the presence of an aural performance error midway through the piece (Video 3); the same error accompanied by a negative facial reaction by the performer (Video 4); the facial reaction with no corresponding aural error (Video 5). The participants were 53 musicians and 52 non-musicians (N=105) who individually assessed the performance quality of one of the five randomly assigned videos via a digital continuous measurement interface and headphones. The results showed that participants viewing the ‘inappropriate’ stage entrance made judgments significantly more quickly than those viewing the ‘appropriate’ entrance, and while the poor entrance caused significantly lower initial scores among those with musical training, the effect did not persist long into the performance. The aural error caused an immediate drop in quality judgments that persisted to a lower final score only when accompanied by the frustrated facial expression from the pianist; the performance error alone caused a temporary drop only in the musicians’ ratings, and the negative facial reaction alone caused no reaction regardless of participants’ musical experience. These findings demonstrate the importance of visual information in forming evaluative and aesthetic judgments in musical contexts and highlight how visual cues dynamically influence those judgments over time.